The role of Tris(2-carboxyethyl)phosphine reducing agent in the controlled formation of α,ω-Alkanedithiols Monolayers on Au(111) with monocoordinated and bicoordinated configurations - Euti, Esteban (2016)
The addition of the reducing agent tris(2-carboxyethyl) phosphine (TCEP) during the formation of α,ω-alkanedithiols monolayers on Au(111) using the immersion method produces the assembly of monolayers with bicoordinated molecules (both S-terminal groups bound to the surface) that have a reductive desorption potential that is more positive than for monolayers with monocoordinated molecules in a standing up configuration. We show that the use of TCEP either during formation of the monolayer or as a post treatment procedure allows the controlled formation of monolayers with bicoordinated or monocoordinated configurations. Density Functional Theory (DFT) calculations were performed to elucidate the role of TCEP in the formation of the bicoordinated configuration. We investigated the TCEP-dithiol interaction in ethanol solvent as well as the coadsorption of trimethylphosphine with 1,2-ethanedithiol on Au(111). The Brønsted base character of the phosphine facilitates the H exchange from the −SHgroups of the dithiol to the phosphorous atom of TCEP with very low activation energy barriers, thus allowing the thiolate groups to bind to the Au(111) surface, thus yielding the bicoordinated configuration. Dithiol lifting mechanisms such as H exchange between S atoms and the formation of intra/inter layer disulfide bonds have much higher energy barriers.